Silk Fibroin Hydrogel Reinforced With Magnetic Nanoparticles as an Intelligent Drug Delivery System for Sustained Drug Release - Haghighattalab, Mahsa; Kajbafzadeh, Abdolmohammad; Baghani, Mostafa; Gharehnazifam, Ziba; Jobani, Bahareh Mohammadi; Baniassadi, Majid (Frontiers in Bioengineering and Biotechnology, 2022)
Due to the well-known biocompatibility, tunable biodegradability, and mechanical properties, silk fibroin hydrogel is an exciting material for localized drug delivery systems to decrease the therapy cost, decrease the negative side effects, and increase the efficiency of chemotherapy. However, the lack of remote stimuli response and active drug release behavior has yet to analyze comparatively. In this study, we developed magnetic silk fibroin (SF) hydrogel samples through the facile blending method, loaded with doxorubicin hydrochloride (DOX), and incorporated with different concentrations of iron oxide nanoparticles (IONPs) to investigate the presumable ability of controlled and sustained drug release under the various external magnetic field (EMF). The morphology and rheological properties of SF hydrogel and magnetic SF hydrogel were compared through FESEM images and rheometer analysis. Here, we demonstrated that adding magnetic nanoparticles (MNPs) into SFH decreased the complex viscosity and provided a denser porosity with a smaller pore size matrix structure, which allowed the drug to be released faster in the absence of an EMF. Release kinetic studies show that magnetic SF hydrogel could achieve controlled release of DOX in the presence of an EMF. Furthermore, the drug release from magnetic SF hydrogel decreased in the presence of a static magnetic field (SMF) and an alternating magnetic field (AMF), and the release rate decreased even more with the higher MNPs concentration and magnetic field strength. Subsequently, Wilms' tumor and human fibroblast cells were cultured with almost the same concentration of DOX released in different periods, and cell viability was investigated using MTT assay. MTT results indicated that the Wilms' tumor cells were more resistant to DOX than the human fibroblasts, which the IC50 values were calculated 1.82±0.001 and 2.73±0.004 (μg⁄ml) for human fibroblast and Wilms' tumor cells, respectively. Wilms' tumor cells showed drug resistance in a higher DOX concentration, indicating the importance of controlled drug delivery. These findings suggest that the developed magnetic SFH loaded with DOX holds excellent potential for intelligent drug delivery systems with noninvasive injection and remotely controlled abilities.